The Impact of Venous Stenting on Symptoms and Quality of Life in Patients with Idiopathic Intracranial Hypertension and Spontaneous Cerebrospinal Fluid Leak - Mandloi, Shreya; Nisar, Areeba; Shing, Samuel R.; Kahn, Chase; Benedict, Peter A.; Duffy, Alexander; Naamani, Kareem E.; Bray, David; Gooch, M Reid; Toskala, Elina; Evans, James; Farrell, Christopher; Rosen, Marc; Rabinowitz, Mindy R.; Yuan, Hsiangkuo; Nyquist, Gurston G. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Elevated intracranial pressure can cause skull base defects and a spontaneous cerebrospinal fluid (CSF) leak. Venous sinus stenting (VSS) has emerged as a promising treatment option for patients with a CSF leak in the setting of idiopathic intracranial hypertension (IIH). There is a lack of literature on symptomatology and quality of life (QOL) after VSS for IIH patients with a CSF leak. This study explores the effects of VSS on symptoms and QOL in IIH patients with a CSF leak.This is a retrospective study on patients who have IIH complicated by a CSF leak and underwent VSS. A QOL questionnaire was developed from the migraine disability assessment test and the PROMIS-PI was given to patients included in this study.A total of 10 patients were included in this study. Nine patients underwent endoscopic closure of CSF prior to stent placement and one patient was treated with VSS only. There was no evidence of CSF leak recurrence in this population following VSS. Headaches improved in 5/8, tinnitus in 5/6, and visual disturbance in 4/5 patients. Diamox was discontinued in seven out of eight patients after VSS. There was an improvement in headache-specific questions (p = 0.0140) and overall QOL (p = 0.0061) on the QOL questionnaire.This preliminary study demonstrates that VSS is effective in alleviating many symptoms in IIH patients with a CSF leak, especially headaches. Diamox may be able to be discontinued in many patients following VSS. No CSF leak recurrence was noted in this patient population.
Keywords: idiopathic intracranial hypertension; spontaneous cerebrospinal fluid leak; skull base; venous sinus stenting